Determinants of adolescent reproductive health service quality in rural Asia: a systematic review - Tanjung Sibarani, Lintang; Ronoatmodjo, Sudarto (Universitas Gadjah Mada, 2025)
Purpose: The purpose of this systematic review is to identify and synthesize the determinants of adolescent reproductive health service quality in rural Asian settings, to inform improvements in service delivery. Methods: This study is a systematic review conducted in accordance with PRISMA guidelines to retrieve studies on factors affecting the quality of adolescent reproductive health services in rural Asia. After screening and eligibility assessment, 15 reviewed articles published between 2020 and 2024 met the predefined inclusion criteria and were selected for analysis. These studies encompassed both quantitative and qualitative research designs. Relevant data on determinants of service quality were systematically extracted and analyzed using narrative synthesis to identify, categorize, and summarize recurring themes across the selected literature. Results: The findings reveal that the reviewed studies identified a range of socio-cultural, geographical, and economic factors influencing the quality of adolescent reproductive health services. Socio-cultural factors emerged as prominent determinants, with issues such as stigma, traditional norms, and limited community support discouraging adolescents from utilizing available services. Geographical barriers included long distances to health facilities, inadequate transportation infrastructure, and the scarcity of services in remote areas, all of which constrain adolescents’ access to consistent and high-quality care. Economic challenges were also significant, encompassing both direct and indirect costs that often limit the ability of adolescents and their families to seek and sustain reproductive health services. These findings suggest that an interplay of cultural, spatial, and financial constraints often influences the quality of services in rural Asia. Conclusion: Improving the quality of adolescent reproductive health services in rural Asia requires an integrated approach that addresses socio-cultural, geographic, and economic barriers. Key strategies include promoting community engagement, enhancing service accessibility in remote areas, and reducing financial constraints. These efforts are crucial to ensuring equitable access and better reproductive health outcomes for adolescents in rural settings.